A vida, a morte e aquilo que sobra: os espaços residuais como elementos de uma ecologia comunicacional dos lugares da cidade - Balbi, Thiago Machado (2017)
The so-called residual spaces are the “voids” and “leftovers” of buildings that the cities accumulate as a result of their continuous process of construction and reconstruction. They usually are spatialities without any pre-established use and, therefore, inconvenient and hard to solve. On the other hand, they are constantly appropriated by users, once they configure “available” for a multitude of other uses that can unexpectedly arise in the everyday-life. This contingency inherent to the residual spaces is the horizon of the present research, which proposes a revision in the meaning of this expression. Assuming that the cities places are, like any other artifact, used, reused, and unused, the hypothesis is that any place can be endowed with some “residuality”; in other words, “voids” and “leftovers” do not only characterize the residues of buildings, but variables that destabilize the functional determinations of their uses. The question focuses on how these possible uses – spontaneous and unexpected – make up the “communicational ecology” that weaves relations between the city-user and the cities places; and then, being able to reveal alternatives to a more “lively” city daily, enriched by symbiotics interactions, or a “dead” city daily, parasitized by a merely transmissive communication and, often, coercive. This thesis begins with a reflection about the residue as a link between nature and culture, in order to find manifestations of the “residuality” in the cities places. For the empirical research, a methodological strategy was elaborated combining the experimental practices of the Situationist International and Carlo Ginzburg’s Evidential Paradigm. By mean of this strategy, some places, not all apparently residual spaces, were analyzed. As a theoretical and epistemological foundation, the research is based on authors whose works makes possible to think about “residuality” as a link between nature and culture; such as Vilém Flusser, Michel Serres, Milton Santos, Lucrecia Ferrara, Giorgio Agamben, Gilles Deleuze, Felix Guattari, Gilbert Simondon, among others